A Validated HPTLC Densitometric Method for The Quantitative Determination of Ubidecarenone in Bulk and in Capsule Formulation - Anandakumar Karunakaran; Anjana Elampulakkadu; Ramesh Jayaprakash; Senthilkumar Raju; Meka Dharshini Lakshmiganesh (MPI (Media Pharmaceutica Indonesiana), 2021)
A new, simple, precise, accurate and rapid high performance thin layer chromatographic method has been developed and validated for the estimation of ubidecarenone in bulk and in capsule formulation. The chromatographic separation was performed on aluminium TLC plates precoated with silica gel 60F254 as a stationary phase and methanol:water (7:3) as a mobile phase. Detection was performed densitometrically in the absorbance mode at 280nm for the evaluation of chromatograms. The system has given well sharp peak of ubidecarenone (Rf=0.51±0.02). The linearity of the method was established in the range of 1-6 ng/µL with correlation coefficient (r2) of 0.9995. The method was validated for precision, accuracy, robustness, ruggedness, LOD, and LOQ as per ICH guidelines. The limit of detection was found to be 0.0392 ng/µL, whereas the limit of quantitation was found to be 0.1189 ng/µL. The percentage label claim for ubidecarenone in the capsule formulation was found to be 99.96±0.4703. The accuracy of the method was confirmed by recovery studies. The percentage recovery was found to be in the range of 100.10-101.45% for ubidecarenone. The % RSD value was found to be less than 2. The low %RSD value indicates that there is no interference due to excipients used in the formulation. Hence, the developed method was found to be simple, precise, accurate, and rapid for the analysis of ubidecarenone in bulk and pharmaceutical formulation and it can be effectively applied for the quality control analysis of ubidecarenone in bulk and pharmaceutical formulation.